Questioning media management scholarship: four parables about how to better develop the field. Issue 2 (2nd April 2016) - Picard, Robert G.; Lowe, Gregory Ferrell
ABSTRACT: Media management scholarship has achieved increasing maturity in recent years. While acknowledging significant accomplishment, the essay provides a critical assessment to stimulate discourse in the field about what is needed to achieve next stage development in theorisation and relevance for practice. The authors present four parables to illustrate the importance of what they suggest: (1) benefitting societies as well as media industries, and thus more carefully considering our intended role as researchers and educators, (2) building theory that is multidisciplinary and of broader relevance in the social sciences, (3) broadening the methods we employ in research, and (4) challenging ourselves and our students to be more ambitious in our commitments and intentions.